Analysis of Speaking Problems for English Subject in Islamic Education Department at STIT Aqidah Usymuni Sumenep: English - Moh. Zainol Kamal; Albadri Albadri; Ahmad Effendi (JOEY: Journal of English Ibrahimy, 2025)
This study aimed to describe the problems faced by students of the Islamic Education Department in the English Subject, particularly in their English Speaking skills. The research method used in this study was a qualitative descriptive approach. This study aimed to analyze the problems faced by students in speaking skills during English courses in the Islamic Education Department at STIT Aqidah Usymuni Sumenep. Research data was collected through observation, in-depth interviews with students and course lecturers, as well as documentation of grades and Speaking learning activities. The conclusion of this study revealed that students in the Islamic Education Department at STIT Aqidah Usymuni Sumenep encounter various challenges in developing their English Speaking skills. The main obstacles include a lack of self-confidence, limited vocabulary and grammar, less interactive teaching methods, and a learning environment that do not support active language practice.